Femininity in the Seasons (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2023)
For the first paper of the year, I was forced to think of a time in which I was gendered. After much reflection, I decided to tell the story of how I imprisoned myself to femininity during the time in which I struggled most with my Chronic Depression.For additional context, watch the author's reflection on the piece below.